Doing Business Regional Profile 2017 : Latin America and Caribbean - World Bank Group (World Bank, Washington, DC, 2016)
Doing Business sheds light on how easy or difficult it is for a local entrepreneur to open and run a small to medium-size business when complying with relevant regulations. It measures and tracks changes in regulations affecting 11 areas in the life cycle of a business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting minority investors, paying taxes, trading across borders, enforcing contracts, resolving insolvency and labor market regulation. Doing Business 2017 presents the data for the labor market regulation indicators in an annex. In a series of annual reports Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 190 economies, from Afghanistan to Zimbabwe, over time. The data set covers 48 economies in Sub-Saharan Africa, 32 in Latin America and the Caribbean, 25 in East Asia and the Pacific, 25 in Eastern Europe and Central Asia, 20 in the Middle East and North Africa and 8 in South Asia, as well as 32 OECD high-income economies. This economy profile presents the Doing Business indicators for Afghanistan. To allow useful comparison, it also provides data for other selected economies (comparator economies) for each indicator. The data in this report are current as of June 1, 2016 (except for the paying taxes indicators, which cover the period January–December 2015).